Cinema concept & practice - Dmytryk, Edward (Routledge, Taylor & Francis Group, 2019)
"In this unique study of the process of filmmaking, director Edward Dmytryk blends abstract film theory and the practical realities of feature film production to provide an artful and elegant analysis of the conceptual foundations of filmmaking and film studies. Dmytryk explores the technical principles underlying the craft of filmmaking and how their use is effective in developing the viewer's involvement in the cinematic narrative. Originally published in 1988, this reissue of Dmytryk's classic book includes a new critical introduction by Joe McElhaney"--